Star in the storm - Harlow, Joan Hiatt (New York : Aladdin, 2000)
In 1912, fearing for the safety of her beloved Newfoundland dog Sirius because of a new law outlawing non -sheepherding dogs in her Newfoundland village, twelve- year-old Maggie tries to save him by keeping him hidden.
600
Accelerated Reader AR
Keywords: Newfoundland dog -- Juvenile fiction; Dogs -- Juvenile fiction; Newfoundland and Labrador -- Juvenile fiction